2011
DOI: 10.1186/1756-0500-4-430
|View full text |Cite
|
Sign up to set email alerts
|

Webinar Training: an acceptable, feasible and effective approach for multi-site medical record abstraction: the BOWII experience

Abstract: BackgroundAbstractor training is a key element in creating valid and reliable data collection procedures. The choice between in-person vs. remote or simultaneous vs. sequential abstractor training has considerable consequences for time and resource utilization. We conducted a web-based (webinar) abstractor training session to standardize training across six individual Cancer Research Network (CRN) sites for a study of breast cancer treatment effects in older women (BOWII). The goals of this manuscript are to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…In a health services study implementing a quality improvement program, webinars and in-person trainings were found to have comparable results within a primary care physician sample, and webinars were identified to be more cost-effective and flexible to participant schedules [ 33 ]. Other research has found similar results supporting the preference of using webinar-based training to support clinical system changes such as electronic medical record implementation [ 34 ]. However, webinars are primarily didactic and have limited adaptability to particular participant needs.…”
Section: Discussionsupporting
confidence: 60%
“…In a health services study implementing a quality improvement program, webinars and in-person trainings were found to have comparable results within a primary care physician sample, and webinars were identified to be more cost-effective and flexible to participant schedules [ 33 ]. Other research has found similar results supporting the preference of using webinar-based training to support clinical system changes such as electronic medical record implementation [ 34 ]. However, webinars are primarily didactic and have limited adaptability to particular participant needs.…”
Section: Discussionsupporting
confidence: 60%
“…We collected data elements from electronic sources and through standardized medical record reviews conducted at each site by medical record abstractors trained via web-based technology who entered data directly into a computer-based, menu-driven data collection system [17,18]. The medical record abstractor inter-rater reliability across sites was a weighted average of 95% agreement (range 89%–98%) [18].…”
Section: Methodsmentioning
confidence: 99%
“…The medical record abstractor inter-rater reliability across sites was a weighted average of 95% agreement (range 89%–98%) [18]. A study of medical record reviews conducted during the five years after breast cancer diagnosis showed good inter-rater reliability for the CCI [19] and little bias from comorbidity misclassification [20].…”
Section: Methodsmentioning
confidence: 99%
“…Demographic, health‐related, breast cancer‐related, history of cancer, incident malignancies, and follow‐up for mortality variables were collected from medical records and electronic sources (cancer registry, administrative and clinical records, and National Death Index). Standardized medical record reviews were conducted by trained medical record abstractors, and data were entered directly into a computer‐based, menu‐driven data‐collection system 14…”
Section: Methodsmentioning
confidence: 99%
“…Standardized medical record reviews were conducted by trained medical record abstractors, and data were entered directly into a computer-based, menu-driven data-collection system. 14…”
Section: Data Collectionmentioning
confidence: 99%